The Impact of Physical and Psychological Health of Early Married Behaviors in Adolescents - Meitria Syahadatina Noor; Husnul Fatimah; Fauzie Rahman; Nur Laily; Fahrini Yulidasari (Jurnal Berkala Kesehatan, 2021)
Early marriage is a marriage performed by women under the age of 16. Aluh-Aluh Subdistrict obtained 69 early marriages in 2017 at the highest number in Banjar Regency. Early marriage is one of the causes of perinatal death, abortion, obstetric fistula, cervical cancer, high-risk pregnancy, stress, anxiety, and household harmony. The purpose of this study is to explain the relationship between early marriage with abortion, risky pregnancy, anxiety, and domestic harmony on early marriages in Aluh-Aluh Sub-District, Banjar Regency. This study used an observational analytic design with a cross sectional research design. The study population was 211 married mothers in 2017. The sampling technique in this study was using a purposive sampling with a minimum sample size of 50 people. The results showed that there was no relationship between early marriage and the incidence of abortion (p-value = 1,000) and risky pregnancy (p-value = 0.229) from a physical impact. Furthermore, early marriage also has no relationship with anxiety (p-value = 0.133) as a psychological impact. Meanwhile, domestic harmony has a homogeneous result so statistical tests cannot be carried out. The conclusion of this research is that there is no relationship between early marriage with the incidence of abortion, risky pregnancy, and anxiety in women in Aluh-Aluh Sub-District, Banjar District.